Adverse events of pharmacological interventions for insomnia disorder in adults: a systematic review and network meta-analysis - Changhong Lu; Yuanyuan Geng; Xiaoli Guan; Ying Meng; Mucheng Zhu; Yuan Zhao (Frontiers in Psychiatry)
BackgroundThe clinical decision-making to insomnia drugs should comprehensively weight its risks.ObjectiveTo perform a systematic review and network meta-analysis of randomized controlled trials to compare the AEs associated with different insomnia drugs for adults with insomnia.MethodsWe conducted Bayesian network meta-analyses and fixed-effects Mantel-Haenszel network meta-analyses to estimate the relative safety between treatments.ResultsCompared with placebo, zolpidem (somnolence: relative risk [RR] 1.85; dizziness: RR 2.33; headache: RR 1.26), zopiclone (somnolence: RR 2.02; dizziness: RR 2.33; dysgeusia: RR 7.84), indiplon (somnolence: RR 3.46; dizziness: RR 2.30; headache: RR 1.63), gaboxadol (dizziness: RR 3.44), eszopiclone (somnolence: RR 2.00; dizziness: RR 3.18; dysgeusia: RR 10.54), estazolam (somnolence: RR 2.08), flunitrazepam (somnolence: RR 3.04), flurazepam (somnolence: RR 2.52), lemborexant (somnolence: RR 6.57), nitrazepam (somnolence: RR 3.80), Ramelteon (somnolence: RR 2.19), suvorexant (somnolence: RR 3.32), Temazepam (somnolence: RR 3.77), trazodone (somnolence: RR 2.86), triazolam (somnolence: RR 2.35), and esmirtazapine (somnolence: RR 4.63; dizziness: RR 2.87) had the most harmful profile in nervous system disorders. Additionally, compared to placebo, zolpidem was also found to be associated with dry mouth (RR 1.92) and anxiety (RR 3.32); gaboxadol was associated with nausea/vomiting (RR 3.49); and eszopiclone was associated with dry mouth (RR 4.39). Doxepin was associated with lower risk of headache and somnolence than placebo or/and most of other drugs, and had also a lower rate of AEs. We observed no associations between drugs and the risks of serious AEs including nasopharyngitis, respiratory problem, accidental injury, infection, upper respiratory tract infection, sinusitis, or hematuria.ConclusionsMost drugs were positive associated with nervous system disorders and gastrointestinal disorders. Data on some drugs like flurazepam, nitrazepam, triazolam, and zaleplon in some outcomes were mainly based on limited study with rare event and thus was highly uncertain and do not allow firm conclusions.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022344981.